The lion, the weapon and the warlord: historical evaluation of the early Late Bronze Age Aegean iconography - Franković, Filip; Matić, Uroš (Ägypten und Levante, 2020)
This paper historically examines the depictions of warriors, lion hunters and figures of power and authority dated to the early phases of the Late Bronze Age Aegean. We argue that the depictions of warriors and lion hunters reflect warrior hierarchies of the early Late Bronze Age Aegean. Moreover, we define different types of figures of power and authority and argue that two different and parallel elite iconographies depicting such figures were developed during the Neopalatial period on Crete. We suggest that the antagonism between the two elite groups identifying with two parallel elite iconographies is directly visible in some of the combat scenes. We believe that the two iconographies were also used in the self-representation of different Neopalatial elite groups to negotiate their positions in society. However, we suggest that a new iconographic repertoire emerged from the new social reality with the beginning of the Final Palatial period. Later in the paper we turn to the Greek Mainland to compare warrior hierarchies depicted in representations of combat and lion hunt to the warrior hierarchies attested in the burial record. In our view, originally Cretan themes were actively consumed in the context of the Greek Mainland and used to create new elite identities.